Audit Quality, Capital Intensity, Intellectual Capital, Tax Avoidance: Systematic Literature Review - Yusnidar, Yusnidar; Mukhtaruddin, Mukhtaruddin (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
Tax avoidance is one way to reduce the amount of tax paid by taxpayers by not violating or looking for loopholes in tax rules. With this Systematic Literature Review (SLR), researchers aim to explore trends in the influence of audit quality, capital intensity, and intellectual capital on tax avoidance and identify and analyze audit quality factors, capital intensity, and intellectual capital on tax avoidance by analyzing previous research from 2016 to 2025. The results show that audit quality has no effect on tax avoidance, capital intensity has a positive effect, and intellectual capital also has a positive effect. These findings are useful for policymakers for users who will carry out tax avoidance, and for academics, can be material to be developed in the following research.